Energy management and control for islanded microgrid using multi-agents - Hernandez, Frank Ibarra [UNESP]; Canesin, Carlos Alberto [UNESP]; Zamora, Ramon; Martina, Fransiska; Srivastava, Anurag K (My University, 2013)
This paper presents a multi-agent system for realtime operation of simulated microgrid using the Smart-Grid Test Bed at Washington State University. The multi-agent system (MAS) was developed in JADE (Java Agent DEvelopment Framework) which is a Foundation for Intelligent Physical Agents (FIPA) compliant open source multi-agent platform. The proposed operational strategy is mainly focused on using an appropriate energy management and control strategies to improve the operation of an islanded microgrid, formed by photovoltaic (PV) solar energy, batteries and resistive and rotating machines loads. The focus is on resource management and to avoid impact on loads from abrupt variations or interruption that changes the operating conditions. The management and control of the PV system is performed in JADE, while the microgrid model is simulated in RSCAD/RTDS (Real-Time Digital Simulator). Finally, the outcome of simulation studies demonstrated the feasibility of the proposed multi-agent approach for real-time operation of a microgrid. © 2013 IEEE.
Keywords: Distributed energy resources; Microgrid; Multiagent system; Photovoltaic power systems; Real-time digital simulator; Real-time operation